Pengaruh Blended Learning Terhadap Hasil Belajar Seni Musik Pada Siswa Kelas XI-IPA SMAN 3 Bukittinggi - Ghina Aulanda; Yos Sudarman (FBS Universitas Negeri Padang, 2022)
This study aims to see the effect of the use of blended learning on the learning outcomes of music art in Class XI-MIPA2 SMAN 3 Bukittinggi. This research uses quantitative research with a quasi-experimental method. The research population was all students of class XI, while the samples were 36 students of class XI-MIPA2 who became the experimental class and 36 students of class XI-MIPA6 who became the control class. Sampling was done by cluster sampling. Meanwhile, to test the difference in the effect of learning outcomes from different learning treatments, the t-test is a different test for class reunification, from the post-test results in the experimental and control classes. The results showed that by obtaining the calculated t value at a score of 7.625 compared to the t table at a score of 1.68957 using the SPSS version 16 program, then at arithmetic = 0.05 and df = 35, the calculation of the difference in the average learning outcomes was significant. Because the value of t count on the score = 7.625 is greater than the t-table value of 1.68957. It means count > t table. So the working hypothesis (H1) is accepted, while the null hypothesis (H0) is rejected. With these results, it can be concluded that the application of synchronous blended learning affects the music learning outcomes of students in class XI IPA SMAN 3 Bukittinggi to be higher than using asynchronous blended learning.